2012
DOI: 10.1007/s10965-011-9820-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-mechanical stability of ethylene tetrafluoroethylene alternating copolymer, and modification thereof

Abstract: It is generally accepted that ethylene tetrafluoroethylene alternating copolymers (ETFEs) are exceptionally thermal stable materials. However, we found that ETFEs will decompose to some extent when exposed to heat, especially above 300°C and during a dynamic shear process (thermal mechanical degradation, thermalstress-oxidation synergistic destruction). In this article, the dynamic mechanical degradation of ETFE was first verified by dynamic rheometry with the aid of IR analysis, then a facile, environmental f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Several studies have focused on the degradation of PVDF and ETFE. However, most of the previous studies examined the thermal stability or aging characteristics of the polymers; none focused on their decomposition to obtain F – ions for waste treatment. Only one report, a patent describing monomer production for numerous polymers in supercritical water, noted PVDF as an applicable species, but no specific results were shown.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on the degradation of PVDF and ETFE. However, most of the previous studies examined the thermal stability or aging characteristics of the polymers; none focused on their decomposition to obtain F – ions for waste treatment. Only one report, a patent describing monomer production for numerous polymers in supercritical water, noted PVDF as an applicable species, but no specific results were shown.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 also shows that ETFE is a highly crystalline polymer, crystallinity level based on melt curve is 52.5 %, while on crystallization curve 49.2 %. In addition, we have confirmed that ETFE would degrade as temperature was above 300°C [25]. Based on the above mentioned evidence, we select 270-300°C as experimental temperature range.…”
Section: Resultsmentioning
confidence: 81%